Evaluation of Deep Convolutional Neural Network Architectures for Strawberry Quality Inspection - Sustika, Rika; Subekti, Agus; F. Pardede, Hilman; Suryawati, Endang; Mahendra, Oka; Yuwana, Sandra (International Journal of Engineering and Technology, 2018)
Fruits quality inspection is important task on agriculture industry. Automated inspection using machine and vision technology have been widely used for increasing accuracy and decreasing working cost. Convolutional Neural Network (CNN) is a type of deep learning that had a great success in large scale image and video recognition. In this research, we investigate the effect of different deep convolutional neural network architectures on its accuracy in strawberry grading system (quality inspection). We evaluate different types of existing deep CNN architectures such as AlexNet, MobileNet, GoogLeNet, VGGNet, and Xception, and we compare them with two layers CNN architecture as our baseline. Here, we have done two experiments, the first is two classes strawberry classification and the second is four classes strawberry classification. Results show that VGGNet achieves the best accuracy, while GoogLeNet achieves the most computational efficient architecture. The results are consistent on both two classes classification and four classes classification.Â Â